CRITERIA FOR A COMPRAVISTIC ANALYSIS IN WORKS OF TRANSLATION FROM UZBEK TO ENGLISH (International journal of artificial intelligence, 2025)
The translation of Uzbek literature into English represents a critical conduit for intercultural dialogue, bringing the rich tapestry of Central Asian thought, history, and aesthetics to a global audience. However, the linguistic and cultural distance between Uzbek, a Turkic language with deep Perso-Arabic and Soviet-Russian historical strata, and English, a global Germanic language, presents profound challenges. This article proposes a comprehensive, multi-tiered framework of criteria for the comparative analysis of Uzbek-English literary translations. Moving beyond simplistic notions of "fidelity," the framework is structured into three primary domains: "Linguistic-Cultural Criteria", "Textual-Pragmatic Criteria", and "Paratextual-Sociohistorical Criteria". Within these domains, we examine specific analytical points, including the treatment of agglutinative syntax, culturally-bound terms (e.g., "mahalla", "chardaq", "navruz"), honorifics, proverbs, and the translation of the distinct rhythmic and metaphorical systems of Uzbek poetry. The application of this framework is demonstrated through comparative case studies of existing translations of works by authors such as Abdullah Qodiriy, Chulpon, and Otabek Omon. The article argues that a rigorous comparative analysis, grounded in this detailed criteria set, is essential not only for evaluating the quality of individual translations but also for understanding the broader project of world literature and the dynamics of representing a "minor" culture through the lens of a hegemonic language. It concludes that the most successful translations are those that achieve a symbiotic balance between accessibility for the English-language reader and the preservation of the unique cultural and aesthetic "otherness" of the Uzbek source text.